Impact of TP53 mutation status on systemic treatment outcome in ALK-rearranged non-small-cell lung cancer. (23rd August 2018) - Kron, A; Alidousty, C; Scheffler, M; Merkelbach-Bruse, S; Seidel, D; Riedel, R; Ihle, M A; Michels, S; Nogova, L; Fassunke, J; Heydt, C; Kron, F; et al.
Abstract: Background: We analyzed whether co-occurring mutations influence the outcome of systemic therapy in ALK -rearranged non-small-cell lung cancer (NSCLC). Patients and methods: ALK -rearranged stage IIIB/IV NSCLC patients were analyzed with next-generation sequencing and fluorescence in situ hybridization analyses on a centralized diagnostic platform. Median progression-free survival (PFS) and overall survival (OS) were determined in the total cohort and in treatment-related sub-cohorts. Cox regression analyses were carried out to exclude confounders. Results: Among 216 patients with ALK -rearranged NSCLC, the frequency of pathogenic TP53 mutations was 23.8%, while other co-occurring mutations were rare events. In ALK/TP53 co-mutated patients, median PFS and OS were significantly lower compared with TP53 wildtype patients [PFS 3.9 months (95% CI: 2.4–5.6) versus 10.3 months (95% CI: 8.6–12.0), P < 0.001; OS 15.0 months (95% CI: 5.0–24.9) versus 50.0 months (95% CI: 22.9–77.1), P = 0.002]. This difference was confirmed in all treatment-related subgroups including chemotherapy only [PFS first-line chemotherapy 2.6 months (95% CI: 1.3–4.1) versus 6.2 months (95% CI: 1.8–10.5), P = 0.021; OS 2.0 months (95% CI: 0.0–4.6) versus 9.0 months (95% CI: 6.1–11.9), P = 0.035], crizotinib plus chemotherapy [PFS crizotinib 5.0 months (95% CI: 2.9–7.2) versus 14.0 months (95% CI: 8.0–20.1), P < 0.001; OS 17.0 months (95% CI: 6.7–27.3) versus not reached, P = 0.049] and crizotinib followed by next-generation ALK-inhibitor [PFS next-generation inhibitor 5.4 months (95% CI: 0.1–10.7) versus 9.9 months (95% CI: 6.4–13.5), P = 0.039; OS 7.0 months versus 50.0 months (95% CI: not reached), P = 0.001). Conclusions: In ALK -rearranged NSCLC co-occurring TP53 mutations predict an unfavorable outcome of systemic therapy. Our observations encourage future research to understand the underlying molecular mechanisms and to improve treatment outcome of the ALK/TP53 co-mutated subgroup.